The cultural pages of comics: cross-cultural variation in page layouts. Issue 1 (2nd January 2019) - Cohn, Neil; Axnér, Jessika; Diercks, Michaela; Yeh, Rebecca; Pederson, Kaitlin
ABSTRACT: Page layouts are a salient feature of comics, which have only recently begun to be studied using empirical methods. This preliminary study uses corpus analysis to investigate the properties of page layouts in comics from Europe (Sweden, France), Asia (Japan, Hong Kong), and America (Mainstream, Indy genres). Pages from Asian books used more vertical segments and bleeding panels, while European and American Indy pages used more horizontal staggering. Pages from American mainstream comics used widescreen panels spanning a whole row, and more variable distances between panels (separation, overlap). These results suggest that pages from different types of comics have different systematic characteristics, which can be studied by empirical methods.